Biomechanical analysis of the change in pistol shooting format in modern pentathlon - Dadswell, C. E.; Payton, C.; Holmes, P.; Burden, A. (Journal of Sports Sciences, 2013)
Despite the importance of the Combined Event to the modern pentathlon competition, little is known about performance in the event. This study aimed to (i) identify the key variables affecting Combined Event shooting performance, and the extent to which these corresponded with those identified for precision shooting and (ii) investigate the impact of changing shooting format, and whether more successful precision shooters were also more successful in the Combined Event. Seven modern pentathletes and three pistol shooters completed precision and Combined Event trials. An opto-electronic shooting system recorded score and pistol movements, whilst force platforms recorded centre of pressure movements 1 s prior to every shot. Intra-individual analysis revealed that the extent of associations between variables was participant-specific, highlighting the need for individual analysis of performance. No participants displayed matching associations between variables for precision and Combined Event shooting, emphasising the difference between performances in the two events. Both groups experienced significantly reduced scores, and increased pistol and body movements for Combined Event shooting (P < 0.05). Despite the pistol shooters` greater precision shooting ability, no significant differences were evident between the groups` Combined Event performances (P > 0.05). This implies that experience in one event does not guarantee success in the other, indicating the importance of event specific training.